Islamic finance principles & applications - Muhammad, Junaina; Mohammed Shah, Sabarina; Mahat, Fauziah; Abdullah, Amalina (Centre for Global Open Access Learning, Immersive Technology & Quality Assurance, Universiti Sains Islam Malaysia, 2017)
This course is an eye opener to the principles and applications of Islamic finance. It covers the various aspects of Islamic finance principles in the public welfare and profit making transactions. There are four (4) modules to highlight the importance of Islamic finance principles based on Shariah, the importance of waqf and zakat, Islamic Finance contract applications and the role of Islamic Capital Market (ICM) in financing and investing activities. This course delivers and shares knowledge through activities via website tools such as powtoon, mysimpleshow, thinglink and others and interview sessions with scholars and market players.